ASESMEN FORMATIF SEBAGAI INSTRUMEN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Adnan Syah Sitorus; Muhammad Yoggi Aqsal Darmawan; Agus Alfaya Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The learning process is conducted to achieve specific predetermined objectives. To ensure that this process stays on the right track, continuous assessment is essential. However, stagnant and unsustained assessment often occurs in Islamic Religious Education (IRE) learning. The purpose of this study is to understand the role of formative assessment in Islamic Religious Education learning and to find out the role of formative assessment in improving the quality of Islamic Religious Education learning. A qualitative approach with a case study method was employed. Data collection techniques included participatory observation, structured interviews, and documentation, all aimed at obtaining in-depth information regarding formative assessment in IRE. The main informants in this study were three Islamic Religious Education teachers at SD IT Anak Sholeh. The findings reveal that formative assessment serves as a vital tool for educators to continuously monitor students' progress, refine teaching methods, and enhance overall learning outcomes. This assessment is conducted through various activities, including short quizzes, class discussions, and targeted assignments designed to evaluate students' understanding of newly introduced concepts. Within the context of the Merdeka Curriculum, formative assessment empowers students to engage in self-evaluation of their skills and knowledge retention. Despite certain challenges, the implementation of formative assessment at SD IT Anak Sholeh has proven effective, serving not only as an evaluation tool but also as a strategic approach to ensuring that Islamic Religious Education plays a key role in shaping students’ character in alignment with Islamic values.